2013
DOI: 10.1007/s10792-013-9851-2
|View full text |Cite
|
Sign up to set email alerts
|

Pathological findings in enucleated eyes after intravitreal melphalan injection

Abstract: The aim of this study is to evaluate the pathological findings of the eye after intravitreal melphalan for viable vitreous seeding from retinoblastoma. All enucleated eyes receiving an intravitreal injection of melphalan (10-50 μg in 0.05 cc) were evaluated for histological changes. Of 25 treated cases, 8 eyes needed enucleation because of phthisis, parent request, or new tumor development. One of the cases was excluded from the study because of a history of intra-arterial chemotherapy with melphalan. There wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0
3

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 21 publications
1
25
0
3
Order By: Relevance
“…The use of intravitreal chemotherapy to control vitreous seeds — most difficult to control form of retinoblastoma — has been promising, especially in combination with a safety-enhanced injection technique and well defined eligibility criteria. 133,135,136,163,164 Under anaesthesia, the intraocular pressure is lowered by removing a small volume of fluid from the anterior chamber or by digital massage. Melphalan (or combined with topotecan) is injected into the vitreous behind the lens, through the conjunctival, sclera, and pars plana with a small-gauge needle.…”
Section: Managementmentioning
confidence: 99%
“…The use of intravitreal chemotherapy to control vitreous seeds — most difficult to control form of retinoblastoma — has been promising, especially in combination with a safety-enhanced injection technique and well defined eligibility criteria. 133,135,136,163,164 Under anaesthesia, the intraocular pressure is lowered by removing a small volume of fluid from the anterior chamber or by digital massage. Melphalan (or combined with topotecan) is injected into the vitreous behind the lens, through the conjunctival, sclera, and pars plana with a small-gauge needle.…”
Section: Managementmentioning
confidence: 99%
“…Intravitreal melphalan injections directly bypass this barrier and achieve tumoricidal concentrations in the vitreous [4]. While highly effective, intravitreal melphalan injection may in rare cases be associated with serious ocular side effects [6,7]. The case series herein described presents the first examples of acute hemorrhagic retinal toxicity noted within 1 week of intravitreal melphalan injection, without any recognized deviation from the standard technique.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Francis et al [3] demonstrated that weekly injections of melphalan resulted in a dose-dependent decrease in the electroretinogram (ERG) response in both humans and rabbits; thus, they cautioned against doses higher than 30 μg. Ghassemi and Amoli [6] described ischemic necrosis in the retina and choroid, severe gliosis and phthisis bulbi, and secondary neovascularization in a histopathologic analysis of enucleated eyes after receiving 50 μg of intravitreal melphalan. Severe toxicity after intravitreal melphalan injection appears to be rare.…”
Section: Introductionmentioning
confidence: 99%
“…In another study, they showed that of 25 IViC-treated cases, eight eyes needed enucleation because of phthisis, parent request, or new tumor development. There was no case of needle-site scleral involvement by retinoblastoma cells 141,142…”
Section: Clinical Management Of Retinoblastomamentioning
confidence: 98%